Photoactivated Organic Nanomachines for Programmable Enhancement of Antitumor Efficacy. Issue 24 (12th May 2022) - Huang, Xing; Liu, Yang; Feng, Ao; Cheng, Xie; Xiong, Xiangyu; Wang, Zimo; He, Zhaoxia; Guo, Jintang; Wang, Shuai; Yan, Xibo
Abstract: Limited permeability in solid tumors significantly restricts the anticancer efficacy of nanomedicines. Light‐driven nanomotors powered by photothermal converting engines are appealing carriers for directional drug delivery and simultaneous phototherapy. Nowadays, it is still a great challenge to construct metal‐free photothermal nanomotors for a programmable anticancer treatment. Herein, one kind of photoactivated organic nanomachines is reported with asymmetric geometry assembled by light‐to‐heat converting semiconducting polymer engine and macromolecular anticancer payload through a straightforward nanoprecipitation process. The NIR‐fueled polymer engine can be remotely controlled to power the nanomachines for light‐driven thermophoresis in the liquid media and simultaneously thermal ablating the cancer cells. The great manipulability of the nanomachines allows for programming of their self‐propulsion in the tumor microenvironment for effectively improving cellular uptake and tumor penetration of the anticancer payload. Taking the benefit from this behavior, a programmed treatment process is established at a low drug dose and a low photothermal temperature for significantly enhancing the antitumor efficacy. Abstract : Photoactivated organic nanomachines are powered by an NIR‐fueled organic semiconducting polymer engine for light‐driven traversing of physiological barriers in the tumor microenvironment. The great manipulability of the organic nanomachines allows precise programming of the antitumor treatment for significantly enhanced efficacy at a low drug dose and a low photothermal temperature.